Strategi Content Marketing Syariah Toko Abata Donat Melalui Media Sosial Instagram @Abatadonuts dalam Membangun Brand Awareness - Infantri, Riski Saeful; Rahmadiva, Lelita Azaria (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
The development of social media as a digital marketing platform encourages culinary businesses to implement content marketing strategies that enhance brand awareness. In sharia-based businesses, a key challenge lies in consistently integrating Islamic values into digital marketing practices. This study aims to analyze the sharia-based content marketing strategy implemented by the Instagram account @abatadonuts in building brand awareness. The research employs a qualitative method with a case study approach. Data were collected through Instagram content observation, in-depth interviews with the informants consisting of the business owner and social media management staff, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman, with data validity ensured through source triangulation. The findings indicate that sharia-based content marketing is manifested through transparent product promotion, the delivery of da’wah and Islamic values, the use of testimonials, educational content, and behind-the-scenes posts. The integration of honesty, trustworthiness, and information transparency contributes to strengthening brand recognition and brand recall. This study provides theoretical and practical contributions to the development of sharia-based content marketing for culinary MSMEs utilizing social media.